(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the role of Science and Nature Centers, established under the “Ilk kadam” state program, in fostering the holistic development of preschool children. The study explores how interactive, nature-based, and inquiry-driven learning environments stimulate cognitive growth, emotional well-being, social skills, and environmental awareness among young learners. Through hands-on experiments, observation, and guided exploration, children develop curiosity, problem-solving abilities, and respect for nature, while teachers act as facilitators of active learning rather than traditional instructors